Abundancia de Lytechinus variegatus (Echinoidea: Toxopneustidae) en la isla de Cubagua, Venezuela - Gómez Gaspar, Alfredo (2000)
The sea urchin roe is among the highest valued seafood items in the world. Increasing demand has extended this fishery worldwide and cases of overfishing have been detected in some countries. On the eastern coast of Venezuela some species of sea urchin, such as Lytechinus variegatus, are consumed as food but studies to determine the abundance and size do no exist. Between February 1998 and April 1999 six sampling stations (depth under 5 m) in Cubagua island (perimeter 25 km) were visited in 11 occasions to study the population density of L. variegatus, with a 0.25 m2 quadrat thrown eight times over seagrass (Thalassia testudinum) beds. Temperature was determined on site, and water samples for salinity and dissolved oxygen concentration were collected. Each specimen was measured and returned to the sea. Diameter range was 8.6 to 74.2 mm (n=3 404) and mean size 26.56-55.34 mm. On the northern coast density varied from 2 to 23 urchins 1m2; on the eastern coast from 15 to 82 /m2 and from 21 to 58 /m2 on the southern coast. On the north coast the seagrass beds are scarce.